Thrombocytopenia following implantation of different types of bioprosthetic aortic valves in severe aortic valve stenosis replacement. (3rd October 2022) - Lampropoulos, K; Toulgaridis, F; Niarchou, P; Bazoukis, G; Mililis, P; Tyrovolas, K; Kanellos, I; Tse, G; Argyriou, M; Dedeilias, P; Charitos, C
Abstract: Aim: The use of bioprosthetic valves in the surgical aortic valve replacement (SAVR) or transcatheter aortic valve implantation (TAVI) of severe aortic stenosis has been associated with post-implantation thrombocytopenia, usually reversible and rarely combined with severe bleeding events. The purpose of this study was to compare the grade of thrombocytopenia and the presence of bleeding events following the implantation of bioprosthetic valves, where either surgery (Solo, Perceval, Trifecta) or transcatheter method (self-expandable TAVI) was followed. Methods: 89 patients with severe aortic stenosis were included in the study. All patients underwent either SAVR or TAVI. In each group 3 different types of bioprosthetic valves were used [59 patients in SAVR group: Solo (14), Perceval (27), Trifecta (18), 30 patients in TAVI group: Evolut R (10), Portico (15), Acurate (5)]. All patients had normal or slightly reduced platelet count at baseline. Patients previously receiving anticoagulants, patients with a primary blood disorder affecting the number of platelets, as well as patients with a post-surgery complication that could affect the number of platelets (e.g., HIT syndrome, etc.) were excluded from the study. Blood samples were taken in the morning before intervention and every morning during the first week of follow-up. Platelet count values before and after implantation were compared with paired t-test (SPSS V21.0, Inc., Chicago, IL, USA), while the reduction of platelets was compared between the 4 different valves with independent t-test. P-values of <0.05 were considered significant. Results: Mean age was 76.8±5.1 years. There was no statistically significant difference between the 2 groups of patients concerning the baseline characteristics and the administered anticoagulants. Statistically significant reduction of the blood count was observed in all groups [Solo: 136±80x10 3 /μl (p=0.009), Perceval: 129±75x10 3 /μl (p<0.001), Trifecta: 74±32x10 3 /μl (p<0.001, TAVI: 60±103μl)]. There was no observed statistically significant difference between Solo and Perceval group (p=0.85) or Solo and Trifecta group (p=0.053), but in the case of Perceval and Trifecta group, a statistically significant difference was noted (p=0.047). A statistically significant difference in both SAVR and TAVI groups was demonstrated (p=0.040) regarding blood count reduction. There was no occurrence of any major bleeding events. 3 patients (3.3%) presented mild bleeding disorders (1 patient epistaxis and 2 patients mild hematuria). Conclusion: Both methods, surgical and transcatheter severe aortic stenosis replacement and all the different bioprosthetic valves that were implanted, were associated with statistically significant reduction of platelet count post-implantation. This reduction was linked to the procedure due to endothelial damage, shear stress injury, inflammation-related platelet consumption, and was not associated with clinically significant bleeding events. Funding Acknowledgement: Type of funding sources: None.